Pengaruh usia dan jenis kelamin Terhadap periodontitis - Khairunnisya, Anzani; Erawati, Jeti; Nursolihati, Vidya (Jurnal Kedokteran Gigi Terpadu, 2025)
Background: Periodontitis is a chronic inflammatory disease that affects the supporting structures of the teeth, characterized by progressive destruction of the periodontal ligament and alveolar bone. The severity of this condition is influenced by various factors, including age and sex. Objectives: To observe the influence of age and sex on periodontitis. Methods: This article reviews several literature regarding the influence of age and sex on progression of periodontitis. Results: As age increases, there is a decline in the regenerative capacity of tissues, along with greater exposure to risk factors such as plaque accumulation, systemic diseases, and a weakened immune response, all of which contribute to the progression of periodontitis. In addition, sex also plays a role, with males and female equally showed influence on the progression of periodontitis.